Managing people in today's law firm : the human resources approach to surviving change - Weisbord, Ellen (Quorum Books, 1995)
Annotation "Managing People in Today's Law Firm: The Human Resources Approach to Surviving Change provides a comprehensive treatment of critical aspects of modern management: motivation, communication, organizational culture, structure and strategy, power and politics, recruitment and training, the reward-performance-retention dynamic, performance appraisal, and planned change. Grounded in managerial theory and research, based on extensive practice, and exemplified by anecdotal "war stories," this book makes valuable reading for partners, associates, managers, and future members of law firms - and offers important ideas for motivating members of all professional service firms."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved